Pengaruh Pengungkapan Islamic Social Reporting Terhadap Profitabilitas Pada Jakarta Islamic Index (JII) Periode 2022-2024 - Mila Santi; Atika Lusi Tania; Era Yudistira; Lella Anita (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the effect of Islamic Social Reporting (ISR) disclosure on the profitability of companies listed on the Jakarta Islamic Index (JII) during the period 2022–2024. A quantitative associative method was used with a sample of 20 companies through purposive sampling, utilizing secondary data from sustainability reports, annual reports, and the official website of the Indonesia Stock Exchange. The results showed that ISR had no significant effect on Gross Profit Margin (GPM), as GPM only reflects gross profit as the difference between sales and cost of goods sold. Therefore, ISR activities such as zakat, donations, or sharia reporting do not affect the core production cost structure. Conversely, ISR had a positive and significant effect on Net Profit Margin (NPM), with a significance value of 0.043, indicating that increased ISR disclosure can increase a company's net profit. This finding confirms that ISR influences final profitability more through reputation and overall cost efficiency, providing strategic implications for companies, investors, and regulators in supporting sustainability based on Islamic principles.